(untitled) (Cinéma & Cie. Film and Media Studies Journal, 2016)
What comes after post-cinema? Such a question calls for speculation as a central mode of inquiry. However, this speculative turn is engaged not only by the question of what comes after the ‘post’; for post-cinema, at its best, is itself already a speculative term — despite the fact that it grows, historically, out of theories of loss (the loss of the index, the end of celluloid, the demise of cinema as an institution). Against this backdrop of mourning and melancholia, postcinema is speculative in at least two senses. First, the concept of post-cinema is future-oriented at root, as it purports to gain purchase on movements along an unfinished trajectory, hence speculating of necessity about its own future course as a determinant of present actuality. Second, post-cinema refers to media engaged materially in a speculative probing of the present. The ‘presence’ of experience is now more radically than ever — because materially, medially — dispersed, not just as a play of signifiers but across and within an ecology that is materially redefining the parameters for life and agency itself in post-cinematic times. Accordingly, the question of post-cinema’s passing is the question of time’s passing in the space of post-perceptual mediation.